Bracken Fern Control in Pastures: SS-AGR-357/AG366, rev. 8/2021 - Sellers, Brent A.; Ferrell, Jason; Wilson, Tim (EDIS, 2021)
This publication discusses chemical control of bracken fern in pastures. Written by B. Sellers, J. Ferrell, and T. Wilson, and published by the UF/IFAS Agronomy Department, revised August 2021.